THE IMPACT OF INTERNAL CONFLICTS IN SYRIA AND IRAQ ON THE SECURITY COMPLEX IN THE MIDDLE EAST (2011-2023) - Abdou , Ahmed; Taib, Tariq (Humanities Journal of University of Zakho, 2024)
Starting in 2011, a series of uprisings led to internal changes in many countries of the Arab world, which influenced Geirangers Daniel, who then perfected those innovations in Syria and Iraq. The study here focuses on exploring the impact of politics on internal relations and anticipating its potential impact on the following advantages and benefits. This study aims to analyze and explain the extent to which the internal conflicts in Syria and Iraq have affected an increasing level of specialized vehicles in the Middle East. The study confirms that the more the internal conflicts in Syria and Iraq are interconnected and allied, that is, they affect the conflict and competition between the final interlocutors and their exit. Which reflects on the Gulf and the Levant and affects the international region? To verify the validity of the initial hypothesis of our study, we carried out multiple investigations, focusing on deductive models, analytical framework, and historical context..